2008
DOI: 10.1590/s1516-89132008000100014
|View full text |Cite
|
Sign up to set email alerts
|

Bulliform cells in Loudetiopsis chrysothrix (Nees) Conert and Tristachya leiostachya Nees (Poaceae): structure in relation to function

Abstract: This work reports anatomic and ultrastructural characteristics of bulliform cells in Loudetiopsis chrysothrix

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
46
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(51 citation statements)
references
References 19 publications
(18 reference statements)
1
46
0
2
Order By: Relevance
“…Several studies had shown the increase of sclerenchyma in response to low water availability (Bacelar et al, 2004), an alteration that is important for the plants to avoid water loss. The first cycles produced higher quantity of this tissue, which shows a possible attempt to save water, since these cycles showed a more vulnerable vascular system than the last cycles.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies had shown the increase of sclerenchyma in response to low water availability (Bacelar et al, 2004), an alteration that is important for the plants to avoid water loss. The first cycles produced higher quantity of this tissue, which shows a possible attempt to save water, since these cycles showed a more vulnerable vascular system than the last cycles.…”
Section: Resultsmentioning
confidence: 99%
“…A greater number of bulliform cells with bigger polar diameter in the initial cycles is possibly related to leaf curling, which leads to a decrease in the transpiration surface area (Alvarez et al, 2008). This fact is important at the initial cycles, because they are more sensitive to flooding.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that under drought conditions, bulliform cells lose turgor pressure and shrink, leading to the rolling up of leaves. Once water is sufficient, the bulliform cells expand and the leaves open again (Price et al, 1997;Alvarez et al, 2008). However, the molecular and genetic mechanisms of leaf rolling and the function of bulliform cells in leaf rolling remain to be elucidated.…”
mentioning
confidence: 99%
“…Leaf tissues such as epidermal and/or bulliform cells possess large vacuoles (Alvarez et al 2008;Moulia 2000) which serve as a dump for high amount of Na ? /Cl -ions that are transported to the leaves under stress conditions, to protect physiologically active mesophyll cells (Tester and Davenport 2003).…”
Section: Introductionmentioning
confidence: 99%